Authentic Assessment in Kurikulum Merdeka: Benefits, Challenges, and Implementation Strategies - Ramadhani Robi'ah, Wisda (Samudra Publisher, 2025)
Authentic assessment plays a crucial role in enhancing the relevance and effectiveness of education, particularly within the framework of Kurikulum Merdeka. This study aims to explore the benefits, challenges, and implementation strategies of authentic assessment in Indonesian schools. Using a qualitative approach through a systematic literature review, data were collected from scholarly articles, academic books, and official documents. The findings reveal that authentic assessment enhances student engagement, motivation, 21st-century skills, and provides actionable feedback for continuous improvement. Key challenges include significant time and resource requirements, maintaining consistent assessment standards, and the lack of teacher training. Proposed strategies include professional development programs, resource allocation, and the development of comprehensive guidelines. These findings highlight the importance of support systems to ensure the effective integration of authentic assessment, aligning with Kurikulum Merdeka’s goal of preparing students for real-world challenges.